1995
DOI: 10.1161/01.str.26.6.1014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Static and Dynamic Cerebral Autoregulation Measurements

Abstract: These data show that in normal human subjects measurement of dynamic autoregulation yields similar results as static testing of intact and pharmacologically impaired autoregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
1,048
6
16

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 796 publications
(1,104 citation statements)
references
References 32 publications
34
1,048
6
16
Order By: Relevance
“…Cerebral autoregulation dynamics are usually evaluated by the changes in BFV and BP during the interventions that induce rapid BP reductions or increases such as the Valsalva maneuver, thigh cuff deflation and the head-up tilt [2,9,50,[60][61][62][63]. The conventional approach is valuable, because it allows assessments of the autoregulation responses during rapid variations in systemic pressure under the stressed conditions.…”
Section: Ivc Assessment Of Cerebral Autoregulation From Spontaneousmentioning
confidence: 99%
“…Cerebral autoregulation dynamics are usually evaluated by the changes in BFV and BP during the interventions that induce rapid BP reductions or increases such as the Valsalva maneuver, thigh cuff deflation and the head-up tilt [2,9,50,[60][61][62][63]. The conventional approach is valuable, because it allows assessments of the autoregulation responses during rapid variations in systemic pressure under the stressed conditions.…”
Section: Ivc Assessment Of Cerebral Autoregulation From Spontaneousmentioning
confidence: 99%
“…The final value of the models response (both linear and non linear) after applying an idealised step (see Figure 2A) is a commonly used approach [6,8,26] to assess CA , and will be denoted as FVS (Final Value from the Step); in absent CA, FVS remains elevated [15]. Also, the amplitude at 3 seconds was calculated and expressed as a percentage change from the initial segment of the response (amplitude at 1 second) -denoted PCS (Percentage Change from the Step), as this was shown to be more robust than FVS [6].…”
Section: Selection Of Autoregulatory Parametersmentioning
confidence: 99%
“…Figure 2B and 3A show the expected left-shift (phase lead) in the PPR [7] resulting from the high-pass characteristics of the autoregulatory response [5,14]. Results from preliminary work [13] based on simulations using Tiecks model [15] and recorded data showed that the PPR at 1.5 seconds (A1.5) and the amplitude at 7 seconds (A7) (as shown in Fig. 3A) provide good separation of different levels of CA and are thus selected for inclusion in the current study.…”
Section: Selection Of Autoregulatory Parametersmentioning
confidence: 99%
See 2 more Smart Citations